EFEKTIFITAS PENGELOLAAN KEUANGAN DESA (STUDI KASUS DI DESA PURWODADI KECAMATAN TEGALREJO KABUPATEN MAGELANG) - Nuwun Priyono; Muhamad Wahyudi; Whinarko Juli Prijanto (Among Makarti, STIE AMA Salatiga, 2019)
AbstractAccording to UU Number 6 of 2014 concerning Villages, villages have received sources of income from the State Budget. There is a need to research the HR in managing village finance and various other things that are obstacles. The objectives of this study are: 1) Analyzing the effectiveness of village financial management in Purwodadi Village, Tegalrejo Subdistrict, Magelang District, 2) Analyzing and reviewing village financial management mechanisms in Purwodadi Village, Tegalrejo Subdistrict, Magelang District, 3) Knowing the development of financial performance in Purwodadi Village, Tegalrejo District, Magelang and 4) Knowing the efforts made in dealing with the constraints of village financial management in Purwodadi, Tegalrejo Subdistrict, Magelang Regency. The output of this study is expected to produce texts sent to national journals and materials that can be used as enrichment of teaching materials in public sector accounting courses. The data used in this study are primary and secondary data, which will be taken through interviews, questionnaires and observations. Balance sheet report data and APBDes realization report data come from the Purwodadi Village Government, Tegalrejo Subdistrict, Magelang Regency This study uses time series data, namely data from 2015 and 2016. This study will be analyzed using descriptive statistical analysis. By looking at the effectiveness ratio of financial management and measuring village financial performance. The results showed that: 1) based on the APBDes realization report in 2015-2017 village financial management showed an average of 100% which means effective, 2) the development of village financial performance seen from the realization of the APBDes always increasing from 2015-2017, 3) Purwodadi Village's financial management mechanism includes several stages, namely: planning, implementation, administration and reporting and accountability, 4) several efforts have been made by the Purwodadi Village Government in overcoming obstacles and obstacles in managing village finances. Keywords: Efektivitas, Pengelolaan, Keuangan Desa, APBDes